PERSPEKTIF FILSAFAT ILMU TERHADAP PSIKOLOGI BELAJAR ANAK DALAM PROSES MENCARI PENGETAHUAN - Rita Eka Izzaty (Paradigma, 2006)
Science began from the human admiration to both large and small scopes of nature. Human being as rational animal is equipped with curiosity. The characteristic of curiosity can be seen at their childhood. With simple questions to ask is a sign of desire to start to learn and to understand the universe. To have philosophy is essentially a trip to remember any activity everyone had done and enjoyed in their childhood. One of the appropriate ways to go into philosophical world is to pay attention to the children’s questions. There is simple truth, yet important. From children themselves, adults can find wisdom to educate them by stimulating their potention.A psychological study based on epistemological approach is a good andsignificant bridge for educators and parents to understand children in their philosophical questions as efforts to learn finding the truth through science and knowledge. Furthermore, consistent with the cognitive concept in Psychology of Learning, the way to give meaning on the responses we given to the children’s questions should be understood as a causa of the response. Therefore, the use of reason and sensorial meaning in children will be formed early. One of the ways is giving opportunity for children to make identification on their own questions, namely by giving responses that can stimulate their thought. It is significant to develop their own ideas so that they will continuously grow in using thinking levels from the simple to complex ones.Keywords : epistemology, psychology of learning, knowledge, children